ENGLISH PHONOLOGICAL PROCESSES A STUDY OF GENERATIVE PHONOLOGY THEORY - J Sutomo (Dinamika Bahasa dan Budaya, 2012)
English phonological processes happen both in word and phrase levels. In the word level, it occurs when a morpheme is combined with another morpheme. One of the sound will experience a change because of the influence of the other morpheme. The English phonological process  also occurs in  a phrase level. This change is caused by the influence of syntactic factors. This study aims at explaining the forms of phonological processes of English language that occur in word level, concerning the processes of assimilation  and some other morpho-phonemic changes. In explaining the phonological processes, the writer uses the Generative Phonology Theory which is firstly introduced by Noam Chomsky in 1957. The Generative School of Phonology was founded by Noam Chomsky in the late 1950s.  Its basic premises are that phonological structure reflects the linguistic competence of the individual native speaker to compute a phonetic representation for the potentially infinite number of sentences generated by the syntactic component of the grammar.   Key words: phonological processes, assimilation, morpho-phonemic changes, generative phonology, linguistic competence.